Potential Directions of Strategic Development of Medical Tourism: The Case of the Republic of Croatia - Demonja, Damir; Gredičak, Tatjana (Geographica Pannonica, 2020)
Strategic product development in the offer of specific forms of tourism takes place very dynamically and is an example of using the diversification strategy as the dominant development strategy. Once relatively inelastic market offers, it becomes more elastic and with the market demand realizes new forms of partnership based on meeting the demand of each tourists individually. A large number of tourist offer products are adjusted to a smaller segment of consumers, i.e. tourists. The life span of tourism products and services is relatively short. The research for this paper is of a scientific character; it is motivated by the applicative need and in that sense it is applicable. Within the framework of economic science, the basic goal of the paper is to establish and analyze elements in the market that determine the development of medical tourism. The aim is to explore the place and role of strategic management in the function of products and services distribution for medical tourism. The paper attempts to explore the relevance of the valorization potential of medical tourism in the continuous efforts to improve tourism in the Republic of Croatia. This is shown by an analysis of the implementation of the priority tourism policy measures defined by the Tourism Development Strategy of the Republic of Croatia to 2020, i.e. the implementation of the Action Plan for the Development of Medical Tourism in relation to the anticipated dynamics of the implementation of the proposed programs. Regarding the programs in order to increase the competitiveness of medical tourism, the paper discusses the improvement of quality offers in the field of medical tourism through the implementation of quality, accreditation and certification of health facilities. Also, activities carried out at the current moment in the field of medical tourism in the Republic of Croatia are also shown.